DEVELOPMENTS IN ORAL AND MAXILLOFACIAL SURGERY WITH EMPHASIS ON ORTHOGNATHIC SURGERY (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
Orthognathic surgery, a foundational component of oral and maxillofacial surgery (OMFS), has undergone substantial evolution driven by technological integration. This literature review synthesizes contemporary developments in OMFS, emphasizing digitally-enhanced orthognathic procedures and highlighting innovations that have transformed surgical protocols. Advanced three-dimensional virtual surgical planning (VSP), patient-specific customized osteosynthesis, and computer-assisted surgical simulation have significantly improved functional and aesthetic outcomes. Key findings from recent peer-reviewed studies reveal a paradigm shift toward integrated digital workflows, minimally invasive orthognathic surgery (MIOS), and data-driven outcome protocols. Evidence demonstrates that these technological integrations enhance surgical precision, reduce operative duration, and facilitate superior skeletal stability while optimizing airway dynamics and temporomandibular joint function.